Mobile asthma apps for emerging adults transitioning to college: A scoping review - V. Ann Andreoni; Margaret C. Delaney; Susan McNamee; Elizabeth Huggins; Barbara Velsor-Friedrich (Health Care Transitions)
Background: Limited data exists to direct evidence-based asthma self-care for emerging adults as they transition from pediatric to adult health care. This transition often occurs in the college setting, apart from usual parental and health care support systems. Given the chronic, episodic nature of asthma, it is imperative that emerging adults have essential tools to maintain disease control. Objective: A scoping review was conducted to discover if mobile applications (apps) for asthma self-care and management exist for college students between 17 and 25 years of age. Results: Research studies (n = 456) from peer-reviewed journals published between 2015 and 2023 were analyzed. As the search revealed no published articles that met the inclusion criteria for age and educational status, the criteria were revised to eliminate the requirement for college enrollment. Six published articles evaluating 3 separate asthma apps with similar age ranges were identified but without the same educational transition needs. Discussion: The studies reviewed suggested that app use had a positive effect on participants, including ease of information access and improved disease knowledge, symptom control, and/or symptom self-management. Limitations included small sample sizes, participant age variability, and lack of studies on needs specific to emerging adults. Small sample sizes, potential bias due to self-report variability, and inherent bias in cell phone availability in disadvantaged populations limit generalizability. Conclusion: Mobile asthma apps can facilitate transitional care in the emerging adult population. Although this scoping review suggests improved health outcomes with app use, there remains a need for future research on emerging adults with asthma transitioning to college.